Walāya in the formative period of Shi'ism and Sufism: a comparative analysis - Ghofrani, Shayesteh (Routledge Sufi series, 2023)
Introduction -- 1. Walāya in Formative Shiʻism -- 2. Development of Walāya in Formative Shiʻism -- 3. Walāya in Formative Sufism -- 4. Development of Walāya in Formative Sufism -- 5. A Comparative Study of Walāya in Shiʻism and Sufism -- Conclusion -- Bibliography -- Index.